2012
DOI: 10.5402/2012/380412
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Inventory of Forest Fires in Andhra Pradesh, India: Current Status and Conservation Needs

Abstract: Analyzing the spatial extent and distribution of forest fires is essential for sustainable forest management. The present study appraises the distribution of forest fires in one of the largest states in India, Andhra Pradesh, using satellite remote sensing. Advanced Wide Field Sensor (AWiFS) onboard on Indian Remote Sensing Satellite (IRS P6) was used for mapping and analyzing the spatial extent of burnt areas. Comparative analysis was carried out with respect to different forest types, protected areas and acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…A recent assessment for the state of Uttarakhand, in India, found that MODIS and VIIRS based products are only able to identify 5.64% of fire incidents due to their coarse scale (Kalaranjini et al, 2020). Within India, states in Central India (Andhra Pradesh, Chhattisgarh, and Madhya Pradesh) are most regularly affected by forest fires (Reddy et al, 2012), and have a high fire risk (Somashekar et al, 2009). Further, although frequency of forest fires is high in Central India, 55% of total biomass burning in the state of Madhya Pradesh was found to be in croplands, where small property sizes lead to small size of agricultural fires (e.g., Cusworth et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent assessment for the state of Uttarakhand, in India, found that MODIS and VIIRS based products are only able to identify 5.64% of fire incidents due to their coarse scale (Kalaranjini et al, 2020). Within India, states in Central India (Andhra Pradesh, Chhattisgarh, and Madhya Pradesh) are most regularly affected by forest fires (Reddy et al, 2012), and have a high fire risk (Somashekar et al, 2009). Further, although frequency of forest fires is high in Central India, 55% of total biomass burning in the state of Madhya Pradesh was found to be in croplands, where small property sizes lead to small size of agricultural fires (e.g., Cusworth et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The difference in detection was more stark for smaller burn patches (<25 ha) where high resolution data detected 30 times more burned area (Roteta et al, 2019). Therefore, there is an urgent requirement for medium to high resolution fire mapping to better understand fire dynamics in India (Reddy et al, 2012). However, the vast majority of studies in India use MODIS based products or DMSP-OLS data for mapping fires at a coarse resolution (Chand et al, 2007;Singh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in burnt area (from 6,369 km 2 in 2009 to 8,593.5 km 2 in 2012) in Andhra Pradesh has been reported, with the Eastern Ghats and Deccan Plateau being the most affected geographical regions within the state (Reddy et al, 2012). The Eastern Ghats are spread across ~75,000 square kilometers covering the states of Orissa, Andhra Pradesh, southern Tamil Nadu and Karnataka, and have high biodiversity and many species that are endemic to the region (Sandhyarani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The studies in India have utilised moderate resolution AWiFS and high resolution LISS III data (Kodandapani et al 2004;Somashekar et al 2008;Reddy et al 2009Reddy et al , 2012Reddy et al , 2014Sowmya andSomashekar 2010 Harikrishna andSharma et al 2012;Kodandapani 2013;Sudeesh and Reddy 2013;Saranya et al 2014;Satish and Reddy 2016). Near real-time monitoring of active fires is being carried out by National Remote Sensing Centre and Forest Survey of India using coarse resolution MODIS sensor as a part of Indian Forest Fire Response and Assessment System (NRSA 2006).…”
Section: Introductionmentioning
confidence: 99%